2018
DOI: 10.3390/ijms19051307
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Inhibits Haemophilus Parasuis-Induced High-Mobility Group Box 1 Release during Inflammation

Abstract: Haemophilus parasuis (H. parasuis) can cause Glässer’s disease in pigs. However, the molecular mechanism of the inflammation response induced by H. parasuis remains unclear. The high-mobility group box 1 (HMGB1) protein is related to the pathogenesis of various infectious pathogens, but little is known about whether H. parasuis can induce the release of HMGB1 in piglet peripheral blood monocytes. Baicalin displays important anti-inflammatory and anti-microbial activities. In the present study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Baicalin is used clinically in humans and animals because of its antimicrobial, anti-inflammatory, antitumor and antioxidant properties [ 21 , 22 , 23 , 24 ]. Our previously work demonstrated that baicalin has anti–inflammatory effects in G. parasuis -challenged piglets in vivo and in vitro by suppressing inflammatory cytokines and HMGB1 via NF-κB and NLRP3 signaling and reversing apoptosis by altering PKC–MAPK signaling cells [ 25 , 26 , 27 , 28 ]. Baicalin is prominent in the literature on protection of tight junction in epithelial and endothelial cells [ 17 , 29 , 30 ], although high doses of baicalin can reduce tight junction integrity by partly targeting the first PDZ domain of ZO-1 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin is used clinically in humans and animals because of its antimicrobial, anti-inflammatory, antitumor and antioxidant properties [ 21 , 22 , 23 , 24 ]. Our previously work demonstrated that baicalin has anti–inflammatory effects in G. parasuis -challenged piglets in vivo and in vitro by suppressing inflammatory cytokines and HMGB1 via NF-κB and NLRP3 signaling and reversing apoptosis by altering PKC–MAPK signaling cells [ 25 , 26 , 27 , 28 ]. Baicalin is prominent in the literature on protection of tight junction in epithelial and endothelial cells [ 17 , 29 , 30 ], although high doses of baicalin can reduce tight junction integrity by partly targeting the first PDZ domain of ZO-1 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 also participates in systemic fibrotic diseases through the RAGE/MAPK and NF-κB signalling pathways [ 42 ]. In a previous study, we showed that G. parasuis stimulated the release of HMGB1 in piglet PBMNs [ 22 ] and induced the activation of the RAGE and MAPK signalling pathways in porcine aortic vascular endothelial cells [ 20 ]. Therefore, we investigated whether HMGB1 is released and the MAPK signalling pathway is activated in piglets after challenge with G. parasuis .…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin reduced apoptosis triggered by G. parasuis via RAGE, MAPK, and AP-1 in PAVECs [ 20 ]. Baicalin also inhibited PKC-MAPK signalling pathway activation [ 21 ] and attenuated high-mobility group box 1 (HMGB1) secretion [ 22 ] in PMNPs stimulated by G. parasuis . In addition, baicalin could modulate long non-coding RNA and mRNA expression in PAVECs infected by G. parasuis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the anti‐inflammatory effects of baicalin are mediated through the suppression of the NLRP3 inflammasome pathway in a lipopolysaccharide (LPS)‐challenged piglet mononuclear phagocyte model (Ye et al, ). Baicalin also suppresses the secretion of the inflammatory cytokines and HMGB1 via NF‐κB and NLRP3 signaling in Haemophilus parasuis (HPS)‐stimulated piglet cells (Fu, Liu, Chen, et al, ; Fu, Liu, Xu, et al, ; Fu et al, ). Furthermore, baicalin can reverse apoptosis initiated by HPS by altering PKC–MAPK signaling (Ye et al, ).…”
Section: Pharmacokinetic Parameters Of Baicalin Following Single Intrmentioning
confidence: 99%